14 Mitochondria has a role in regulating hypoxic-dependent cell proliferation in pulmonary cells and vascular remodelling. (1st April 1997) - Burzangi, A; Plevin, R; Coats, P
Abstract : Introduction: Hypoxia is a strong contributor to hyper-proliferation of pulmonary artery vascular smooth muscle cells (PAVMSCs) in pulmonary hypertension. 1 The involvement of hypoxia in the PASMC proliferation signalling is poorly understood. The aim of this work was to assess the relationship between hypoxia, PASMC proliferation and vascular remodelling. Methods: PAVSMC were isolated from Sprague Dawley rats. Cells were cultured under hypoxic conditions and compared with normoxic cultures. Cell proliferation stimulated with FCS and PDGF was assessed by 3H -thymidine incorporation assay. Proliferative mRNA markers were measured using real-time qPCR and the phosphorylation of MAP kinases; ERK, JNK and P38 were evaluated using western blot. Mitochondrial DRP-1 inhibitor (mdivi-1) was used as a treatment. Results: Hypoxia (3%) directly enhanced the proliferative of PAVSMCs to 10% FCS and PDGF compared with normoxic cells. Moreover, cells stimulated with 10% FCS display an increase in ERK and p38 MAPK phosphorylation when compared to normoxic cells. PCR data confirms hypoxia induces proliferative genes; increasing mRNA expression of PCNA, ERK1 and P70s6k when compared to normoxic cultures. Inhibiting mitochondrial fission using Mdivi-1 (10 uM) resulted in a significant reduction of PAVSMC proliferation (p<0.05). Under hypoxic conditions, mitochondria dynamics were shifted to mitochondrial fission through a significant increase in mRNA levels of DRP-1 and P22phox compared to normoxic cells. Conclusion: This work confirms hypoxia has directly stimulates PAVSMC proliferation. Significantly mitochondrial function appears to be crucial to hypoxic–dependent PAVSMCs proliferation. Future work will focus on elucidating of the role mitochondria in hypoxic-dependent cell signalling related to PAVSMC and endothelial cell proliferation and migration. Reference: . Pak, et al . Eur Respir J 2007;30:364–72.